Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.